Atributos edáficos como indicadores de qualidade ambiental em área de reflorestamento misto - Goes, João Horacio Dantas Almeida de (2015)
The use of environmental indicators is important to measure and monitor the degree of sustainability of the different models of landscapes, since they are able to report the presence or absence of degradation, and measure disturbances in the sustainability of an ecosystem. Therefore, it is necessary to overview the landscape composition with aspects of spatial distribution of soil characteristics, the dependency relationships with the provision of the terrain and the flora. The present study was conducted in an area with approximately 48 ha, located in Laranjeiras in the state of Sergipe, as a result of an environmental compensation project Votorantim Cimentos have installed in 2005, a mixed reforestation with 31 native species, where previously monoculture of sugarcane was held. After separation of the 30 sample plots to their position in the topossequence (Shoulder, Backslope and Footslope), the experiment was carried through the analysis of soil samples collected at two depths, 0-20 cm, 21-40 cm, as assess the similarities and/or differences between the topographical variations, a comparison was made between the forest tree species in the three topographical points studied, according to the horizontal structure, floristic diversity and diameter distribution. in order to check the influence on the vegetative growth of the species found in the area , as well as analyze, describe and link diversity and structure of the tree component , understanding the behavior , similarities and differences , the settlement of its structure with the relief and soil of the area and its potential as indicators of environmental quality. The analysis of soil samples was compared using the Tukey teste at 5% probability. For chemical analysis, in the 0-20 cm range, the highest average organic matter (34.53 g/dm³), effective CEC (60.35 cmolc/dm³), Sodium (0.407 cmolc/dm³), Potassium (0.216cmolc/dm³), Magnesium (4.35 cmolc/dm³) and Calcium (54.49 cmolc/dm³) were found in the Footslope, the Shoulder showed the highest amount of Phosphorus (30.61 mg/dm³). In the 21-40 cm range, were observed the highest levels of organic matter (21.03 mg/dm³), effective CEC (56.57 cmolc/dm³), Sodium (0.502 cmolc/dm³), Potassium (0.177 cmolc/dm³), Magnesium (4.39 cmolc/dm³), Calcium (51.18 cmolc/dm³) in the Footslope. The highest average Phosphorus (19.69 mg/dm³) was found in the Shoulder. The three species that had the highest IVI in the Shoulder, were Shinus terebinthifolius Raddi (34,93 %), Cassia grandis L.f. (13,19%) and Erythrina velutina Willd. (7,64 %). For Backslope were Shinus terebinthifolius Raddi (28.8%), Cassia grandis L.f. (17,83 %) and Syzygium cumini (L.) Skeels (9,9%). As for the Footslope were Shinus terebinthifolius Raddi (36,08 %), Cassia grandis L.f. (18,12 %) and Lonchocarpus sericeus (Pocr.) Kunth. (8,67%). As for the absolute density, the Shoulder presented the highest value (485 ind / ha), followed by Backslope (468.3 ind / ha) and the Footslope (360 ind / ha), but when viewed BA the Backslope showed the highest value (4.93 m² / ha), followed by Shoulder (4.92 m² / ha) and Footslope (4.29 m² / ha. In general, the terrain was the biggest responsible for the influence on soil chemical properties through the mass flow and deposition of nutrients along the toposequence and is an important source of variation of the tree component, influencing the distribution of species, diversity and representativeness. is an important source of variation of the tree component, influencing the distribution of species, diversity and representativeness. The study revealed that there preference by few species for distinct topossequence environments.